Engineering vibration analysis with application to control systems - Beards, C. F. (Halsted Press, 1996)
Most machines and structures are required to operate with low levels of vibration as smooth running leads to reduced stresses and fatigue and little noise. This book provides a thorough explanation of the principles and methods used to analyse the vibrations of engineering systems, combined with a description of how these techniques and results can be applied to the study of control system dynamics. Numerous worked examples are included, as well as problems with worked solutions, and particular attention is paid to the mathematical modelling of dynamic systems and the derivation of the equations of motion. All engineers, practising and student, should have a good understanding of the methods of analysis available for predicting the vibration response of a system and how it can be modified to produce acceptable results. This text provides an invaluable insight into both.